Incidence of infective endocarditis during the coronavirus disease 2019 pandemic: A nationwide study. (December 2020) - Havers-Borgersen, Eva; Fosbøl, Emil L.; Butt, Jawad H.; Petersen, Jeppe K.; Dalsgaard, Andreas; Kyhl, Frederik; Schou, Morten; Phelps, Matthew; Kragholm, Kristian; Gislason, Gunnar H.; Torp-Pedersen, Christian; Køber, Lars; et al.
Highlights: The incidence of IE during lockdown was 11.1 IE cases per 100, 000 PY. No reduction in the incidence of IE during the lockdown compared to preceding years. No difference in the incidence of IE pre- versus post-lockdown in 2020. Abstract: Background: The incidence of infective endocarditis (IE) has increased in recent decades. Societal lockdown including reorganization of the healthcare system during the COVID-19 pandemic may influence the incidence of IE. This study sets out to investigate the incidence of IE during the Danish national lockdown. Methods: In this nationwide cohort study, patients admitted with IE in either one of two periods A) A combined period of 1 January to 7 May for 2018 and 2019, or B) 1 January to 6 May 2020, were identified using Danish nationwide registries. Weekly incidence rates of IE admissions for the 2018/2019-period and 2020-period were computed and incidence rate ratios (IRR) for 2020-incidence vs 2018/2019-incidence were calculated using Poisson regression analysis. Results: In total, 208 (67.3% men, median age 74.1 years) and 429 (64.1% men, median age 72.7 years) patients were admitted with IE in 2020 and 2018/2019, respectively. No significant difference in incidence rates were found comparing the 2020-period and 2018/2019-period (IRR: 0.96 (95% CI: 0.82–1.14). The overall incidence rate pre-lockdown (week 1–10: 1 January to 11 March 2020) was 14.2 IE cases per 100, 000 person years (95% CI: 12.0–16.9) as compared with 11.4 IE cases per 100, 000 person years (95% CI: 9.1–14.1) during lockdown (week 11–18: 12 March to 6 May 2020) corresponding to an IRR of 0.80 (95% CI: 0.60–1.06) and thus no significant difference pre- versus post-lockdown. Conclusion: In this nationwide cohort study, no significant difference in the incidence of IE admissions during the national lockdown due to the COVID-19 pandemic was found.